The Deterrence Effects of Vicarious Punishments on Corporate Financial Fraud - Yiu, Daphne W.; Xu, Yuehua; Wan, William P. (Organization Science, 2014)
This study extends the research on corporate financial fraud by developing a new perspective on the deterrence effects of vicarious punishments premised on social learning theory. We posit that firms vicariously learn about punishments from their peers by picking up modeling cues, environmental cues, and social cues in the inhibitive learning process, thus being deterred from committing future fraudulence. Using a matched sample of 604 observations of Chinese listed firms between 2002 and 2008, our findings show that an observing firm is deterred from committing fraud if the peers in its industry are caught and punished. We further find that such deterrence effects are subject to how the observing firm evaluates the possibility of being caught and the likelihood it will be punished the same way if it violates similar prohibitions. In particular, inhibitive learning effects are positively moderated by punishments of prominent firms and model–observer similarity but negatively attenuated by the development of the legal system. Our study sheds light on the corporate fraud literature by illuminating the indirect, inhibitive learning process from vicarious punishments and identifying the conditions for differential learning/deterrence outcomes of the observing firms.